Is the devil in the detail? A randomised controlled trial of guided internet-based CBT for perfectionism. (August 2017) - Shafran, Roz; Wade, Tracey D.; Egan, Sarah J.; Kothari, Radha; Allcott-Watson, Hannah; Carlbring, Per; Rozental, Alexander; Andersson, Gerhard
Abstract: An internet guided self-help cognitive-behavioural treatment (ICBT) for perfectionism was recently found to be effective (see this issue). Such studies stand in need of replication. The aim of this study was to report the outcomes and predictors of change when the treatment is delivered in a UK setting. A total of 120 people (Mean = 28.9 years; 79% female) were randomised to receive ICBT or wait-list control over 12 weeks (trial registration: NCT02756871). While there were strong similarities between the current study and its Swedish counterpart, there were also important differences in procedural details. There was a significant impact of the intervention on the primary outcome measure (Frost Multidimensional Perfectionism Scale, Concern over Mistakes subscale) and also on the Clinical Perfectionism Questionnaire (between group effect sizes d = 0.98 (95% CI: 0.60–1.36) and d = 1.04 (95% CI: 0.66–1.43) respectively using intent-to-treat analyses). Unlike the Swedish study, there was significant non-engagement and non-completion of modules with 71% of participants completing fewer than half the modules. The number of modules completed moderated the rate of change in clinical perfectionism over time. In conclusion, the study indicates the intervention is effective in a UK setting but highlighted the importance of procedural details to optimise retention. Highlights: ICBT produced large between group effect sizes. There was a modest but non-significant impact on depression and anxiety. Non-engagement and non-completion rates were higher than the Swedish study (Rozental et al., 2017 ). The number of modules completed moderated the rate of change in clinical perfectionism over time. Those completing more modules had lower clinical perfectionism scores at the end of the intervention.